Austenite/ferrite interface movement during intercritical annealing of a medium Mn steel. Issue 8 (24th May 2021) - Bai, M. K.; Yang, D. P.; Wang, G. D.; Ryu, J. H.; Lee, K. Y.; Misra, R. D. K.; Yi, H. L.
Abstract : The austenite/ferrite interface movement during intercritical annealing of 0.15C–8.0Mn–2.1Al (wt-%) steel was simulated by DICTRA software under local equilibrium and then confirmed experimentally. The simulation results show that the austenite volume fraction exceeds the thermodynamic equilibrium amount during isothermal annealing and then decreases because the interface returns from ferrite to austenite. The reverse interface movement is verified in simulated batch annealing experiment for the first time by ex-situ determining the austenite volume fraction using characterisation of XRD as well as by in-situ measuring the bulk volume change led by phase transformation using dilatometric curves.